Interdisciplinary Approach in Teaching - Application to the Van Der Waals Equation - Kalova, Jana; Ochkov, Valery Fedorovich (2018 IV International Conference on Information Technologies in Engineering Education (Inforino), 2018)
The paper shows how an interdisciplinary approach can be applied in teaching. The approach is called STEM or PMI. We illustrate the advantages of using the software in interdisciplinary subjects. We use the van der Waals equation to show which sort of problems can be solved. We discuss several possible types of teaching, from collaborative or individual learning to the teacher-centered approach. Because the topics are usually complex, we prefer to use some pre-prepared themes.